The Public Power Issue in Charlottetown: An Early Conflict - Holman, Harry (Urban History Review / Revue d'histoire urbaine, 1982)
An electric-power utility was first established in Charlottetown in 1885, but less than fifteen years later the question of its municipalization was being considered. High rates and poor service brought the issue to a head in 1904, and the following year the citizens voted heavily in favour of public power when the question was submitted to them in a plebiscite. Civic politicians proved to be more interested in lower rates than in municipal ownership, however, and when the power company, under duress, promised better but cheaper service, the idea of direct ownership of the utility by the city was quickly forgotten.